Evaluation of storage school storage conditions in schools of the southeast zone of Teresina-Piauí-Brazil (Research, Society and Development, 2020)
The objective of this research was to evaluate the origin and storage conditions of school meals in schools of the municipal network of the southeast zone of Teresina-Piauí-Brazil. The survey was conducted in 46 schools. The questionnaire used was based on the School Lunch Storage Inspection Guide of the Municipality of Fortaleza, Ceará, the questionnaire items were grouped, by subject, into eleven blocks. It was observed that for the block receiving raw material and storage area organization it was found that only 42.0% (ten) and 50.0% (eleven) of the elementary and elementary schools, respectively, present a adequate cold network. For the block physical conditions of the storage area, only 58.0% (fourteen) of elementary schools and 82.0% (eighteen) of elementary school have an exclusive area to store food. For the manipulative block it was found that 46.0% (eleven) and 91.0% (twenty) of the nursery schools of elementary and elementary schools, respectively, use the cap and apron for food handling. In the lectures it was observed that from 46 surveyed schools we had the participation of 76.0% (35 lunch boxes). The main irregularities refer to cold storage conditions, presence of pests in the storage area, existence of exclusive physical area for the storage of groceries, physical structure of the storage area, mainly related to the items walls and doors.